PROCESSO DESIGNATIVO E CONSTRUTO IDENTITÁRIO DA PRIMEIRA-DAMA: PRAGMATISMO E SIMBOLISMO - Ferreira, Dina Maria Martins (Intercâmbio, 2010)
This article points out how feminine identity in mediatic discourse is constructed by means of designation processes. It focuses the relationship between pragmatic and symbolic references; the pragmatic level reveals the politic interests of the historical moment, and the symbolic tries to capsulate the identity in standard valuations.